Quantification of room temperature strengthening of laser shock peened Ni-based superalloy using synchrotron microdiffraction. (September 2022) - Zhou, Guangni; Zhang, Yubin; Pantleon, Wolfgang; Kou, Jiawei; Ramamurty, Upadrasta; Tan, Xipeng; Luo, Sihai; He, Weifeng; Ku, Ching-Shun; Chiang, Ching-Yu; Tamura, Nobumichi; Chen, Kai
Graphical abstract: Highlights: Redundant dislocations are revealed to play a dominant role in laser shock peening induced plastic deformation in Ni-based superalloys. Local dislocation densities in γ and γʹ phases are quantified separately using µXRD in a laser shock peened Ni-based superalloy. A quantitative relationship between micro-scale local hardness increment and dislocation density is established over a millimeter range. Abstract: Laser shock peening (LSP), a surface modification technique, is promising to enhance the strength and wear resistance for Ni-based superalloys. To understand the strengthening mechanism in a laser shock peened Ni-based superalloy DZ417G, we utilize synchrotron poly- and monochromatic X-ray microdiffraction, as well as electron microscopy and microhardness to quantify the local microstructures and mechanical properties at various depths. In the 1.2-mm-deep hardened layer, the microhardness increases monotonically by ∼50% from the unaffected interior to the surface. Quantitative microdiffraction analysis shows that large amounts of dislocations are introduced by LSP. High densities of 7.1 × 10 15 m −2 and 11.8 × 10 15 m −2 are seen close to the peened surface for the γ- and γ′-phases, respectively, which are 5 and 20 times of those in the unaffected region. Different gradients of dislocation density are observed for the two phases from interior to surface, and their combined effect accounts well for the hardness increment. Due to the unaltered γ′-precipitates and chemical composition in the LSP affected zone, the large density of dislocations dominates the observed strengthening. Combined poly- and monochromatic X-ray microdiffraction allows quantifying the local microstructures of plastic deformation over a large sampling scale that can hardly be achieved using other materials characterization techniques.